2018
DOI: 10.1093/geronb/gby041
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Useful Field of View Training on Brain Activity and Connectivity

Abstract: UFOVt enhances connections needed for visual attention. Together with prior work, this study provides evidence that improvement of the brain's visual attention efficiency is one mechanism underlying UFOVt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 46 publications
5
21
0
Order By: Relevance
“…While prior functional studies of the UFOV/Double Decision paradigm found bilateral activation associated with performance, our findings demonstrate right lateralization of structures associated with performance (Ross et al, 2018). This pattern of findings is consistent with other cognitive domains within the context of aging.…”
Section: Right Lateralization Of Findingssupporting
confidence: 84%
See 4 more Smart Citations
“…While prior functional studies of the UFOV/Double Decision paradigm found bilateral activation associated with performance, our findings demonstrate right lateralization of structures associated with performance (Ross et al, 2018). This pattern of findings is consistent with other cognitive domains within the context of aging.…”
Section: Right Lateralization Of Findingssupporting
confidence: 84%
“…Indeed, the role of regions within the CON network in the present study is supported by work from Ross et al, who assessed functional connectivity between numerous ROIs following a UFOV cognitive training intervention (Ross et al, 2018). Of these ROIs, the orbitofrontal cortex and AI demonstrated strengthened functional connectivity and demonstrated increased BOLD activation with better UFOV performance (Ross et al, 2018). Additionally, cortical thickness declines in these regions were significantly associated with poorer Double Decision performance in the present study.…”
Section: Comparison To Prior Findings In the Ufov/double Decision Tasksupporting
confidence: 78%
See 3 more Smart Citations